Conjunctive use in India's Varada River Basin - RAMESH, HONNASIDDAIAH; MAHESHA, AMAI (Journal - American Water Works Association, 2009)
The use of groundwater in conjunction with surface water resources has gained prominence in regions experiencing scarce or uneven distribution of water. In the Varada River Basin in Karnataka, India, for example, an optimization model was developed for the conjunctive use of surface water and groundwater resources because of the increasing demand on agricultural and domestic sectors of this area—s water supply. Monsoon rains, which occur only six months a year, predominantly control the basin—s agricultural activities. However, the area has an immense need for efficient use of available water resources during the rest of the year. The model, based on linear programming, optimizes the allocation of groundwater and surface water subject to hydraulic and stream flow constraints. The model incorporates policy scenarios that add to the sustainability of the system. The developed conjunctive‐use model is simple but effective in computing the optimal use of the Varada basin—s water resources.